EVALUASI KEBIJAKAN OTONOMI KHUSUS DI DISTRIK KUALA KENCANA KABUPATEN MIMIKA PROVINSI PAPUA : STUDI TENTANG PENINGKATAN KUALITAS SDM - Murib, Demianus (Sam Ratulangi University, 2016)
Abstract : The implementation of special autonomy in Papua province has been going forapproximately 15 years. Along with the various programs and assistance for the construction /development of human resources disbursed by the central government. Regional governments are alsothe special autonomy possessed authority to implement various programs and activities for humanresource development of the people of Papua. But the extent of the special autonomy policy has beenable to provide results and positive impact in improving the quality of human resources in Papua?.The interesting question to be answered and analyzed through a scientific investigation, so the authorsraise the title of the study: